Evaluating The Consumer Preference of UHT Ultra Milk Flavor: Evidence from Generation Z Consumers - Santoso, Fellicia Etano; Prastiwi, Wahyu Dyah; Mukson, Mukson (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The existence of different characteristics in each generation encourage producers to stay updated on consumer preferences. This study aimed to analyze the characteristics and preferences of Generation Z consumers for UHT Ultra Milk Flavor. The research was conducted in August – November 2022 using a case study. The sampling method was a purposive sampling of 150 respondents, aged 18-22 years who had consumed Ultra Milk Flavor and purchased at least once in the last week, with pocket money. Data was collected online using Google Forms and then analyzed by descriptive analysis and conjoint analysis. The results showed that Generation Z consumers were dominated by women and the majority of students aged 20 years, with income levels ranging from >IDR 500.000 to IDR 1.000.000, and aware of drinking milk. The type of milk consumed the most is UHT milk with a frequency of purchase of once a week at a minimarket, and is familiar with the use of social media. Overall, the preference for UHT Ultra Milk Flavor is chocolate with 250 ml packaging, price of ≤IDR 5.000 with the most prioritized taste attribute. These findings suggest that milk producers can maintain, improve, and innovate flavors.